Facile Synthesis and Enhanced Photocatalytic Performance of Flower-like ZnO Hierarchical Microstructures - Li, Benxia; Wang, Yanfen (Journal of physical chemistry. C, 2010)
ZnO hierarchical microstructures with uniform flower-like morphology were prepared on a large scale through a template- and surfactant-free low-temperature (80 °C) aqueous solution route. The product was characterized by X-ray diffraction, scanning electron microscopy, transmission electron microscopy, and Brunauer−Emmett−Teller N2 adsorption−desorption analyses. The flower-like ZnO microstructures are assembled by many interleaving nanosheets which have the uniform thickness of about 10 nm and a well-crystalline structure with dominant surfaces as {21̅1̅0} planes. Control experiments revealed that the formation of the flower-like ZnO was based on the fast nucleation−growth kinetics. The flower-like ZnO sample shows an enhanced photocatalytic performance compared with the other nanostructured ZnO powders of nanoparticles, nanosheets, and nanorods, which can be attributed to the special structural feature with an open and porous nanostructured surface layer that significantly facilitates the diffusion and mass transportation of RhB molecules and oxygen species in photochemical reaction of RhB degradation.